2004
DOI: 10.1128/jcm.42.9.3998-4006.2004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Molecular Characterization ofStreptococcus pyogenesRecovered from Scarlet Fever Patients in Central Taiwan from 1996 to 1999

Abstract: One hundred seventy-nine Streptococcus pyogenes isolates recovered from scarlet fever patients from 1996 to 1999 in central Taiwan were characterized by emm, Vir, and pulsed-field gel electrophoresis (PFGE) typing methods. The protocols for Vir and PFGE typing were standardized. A database of the DNA fingerprints for the isolates was established. Nine emm or emm-like genes, 19 Vir patterns, and 26 SmaI PFGE patterns were detected among the isolates. Among the three typing methods, PFGE was the most discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 32 publications
2
38
1
Order By: Relevance
“…It is noticeably shorter than the oneto three-day minimum previously reported [25][26][27][28][29][30]. The procedure reported here was also useful to prepare, in 6hours, immobilized DNA from S. pyogenes in the sample format of the CHEFMapper (BioRad) and to obtain well-resolved patterns.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…It is noticeably shorter than the oneto three-day minimum previously reported [25][26][27][28][29][30]. The procedure reported here was also useful to prepare, in 6hours, immobilized DNA from S. pyogenes in the sample format of the CHEFMapper (BioRad) and to obtain well-resolved patterns.…”
Section: Discussionmentioning
confidence: 87%
“…There are other rapid PFGE protocols reported for subtyping Gram-positive bacteria [19,[23][24][25]34,[43][44][45]. Matushek et al reported a rapid procedure for DNA preparation of Gram-positive bacteria for pulsed field, reducing the incubation times to 4 or 5 hours in some cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). This clonal pattern has also been identified in northern and central Taiwan (4,5). The reemergence of emm12 strains throughout Taiwan may explain the reported increase in cases of scarlet fever noted since 2005.…”
mentioning
confidence: 77%